Community-level internet connectivity and mental health: an analysis of United States counties. (3rd September 2019) - Hatcher, William; Hunter, Lance; Meares, Wesley; Lizotte, Mary-Kate; Avent-Holt, Dustin
Abstract: Background: Access to the Internet is often viewed as a positive feature of communities, but little research has been conducted examining the effects of internet access on mental health at the community level. Aims: To examine the relationship between internet connectivity and mental health in United States (US) counties, an analysis that has not been conducted in the public health literature. Methods: We analyzed predictors of mental health in US counties. Data from the Federal Communications Commission (FCC), the U.S. Bureau of the Census, and the County Health Rankings and Roadmaps were used to construct a time-series regression analysis. The data were available from 2013 to 2016. Results: US counties that increased their internet connectivity over this period also had more citizens report suffering from mental health conditions. Conclusions: Public health needs to focus on the county-level predictors of mental health and how internet connectivity may not always produce positive effects and may be contributing negatively to the mental health of communities.